2021
DOI: 10.4014/jmb.2101.01029
|View full text |Cite
|
Sign up to set email alerts
|

Deoxypodophyllotoxin Inhibits Cell Growth and Induces Apoptosis by Blocking EGFR and MET in Gefitinib-Resistant Non-Small Cell Lung Cancer

Abstract: As one of the major types of lung cancer, non-small cell lung cancer (NSCLC) accounts for the majority of cancer-related deaths worldwide. Treatments for NSCLC includes surgery, chemotherapy, and targeted therapy. Among the targeted therapies, resistance to inhibitors of the epidermal growth factor receptor (EGFR) is common and remains a problem to be solved. MET (hepatocyte growth factor receptor) amplification is one of the major causes of EGFR-tyrosine kinase inhibitor (TKI) resistance. Therefore, there exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…In 2021, Kim used DPT to treat non-small cell lung cancer (NSCLC) and found that DPT could suppress the expression of p -EGFR and p-MET as well as their downs treat proteins p -ErbB3, p -AKT, and p -ERK, and induced high ROS generation. 97…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In 2021, Kim used DPT to treat non-small cell lung cancer (NSCLC) and found that DPT could suppress the expression of p -EGFR and p-MET as well as their downs treat proteins p -ErbB3, p -AKT, and p -ERK, and induced high ROS generation. 97…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…It is well known that the most common hallmarks of cancer cells include sustained proliferation and attenuated apoptosis ( Hanahan and Weinberg, 2011 ). Lately, research has shown that deoxypodophyllotoxin plays an important role in acquired resistance to gefitinib by inducing apoptosis in NSCLC cells ( Kim et al, 2021 ). Consistent with the results, in our study, FYLM downregulated the expression of the apoptosis-related protein Bcl-2 while upregulating the cleaved caspase-3 in a mouse xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have displayed that triggering mitochondria-mediated apoptosis becomes an available method for therapy of resistant cancer. In addition, mitochondria dysfunction could cause the generation of intracellular ROS ( Kim et al, 2021 ), which is confirmed to be involved in the drug resistance related to EGFR and its downstream pathway ( Weng et al, 2018 ; Zhang et al, 2019 ). Excessive ROS produced by external stimuli was not conducive to the survival of cells, thus causing the accumulation of ROS and cell apoptosis ( Yuan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… Young et al (2016) reported that Simvastatin can induce mitochondrial apoptosis to overcome gefitinib resistance with EGFR T790M mutation NSCLC cells. As well known, reactive oxygen species (ROS) formation is closely related to the mitochondrial pathway, which is confirmed to be the cause and/or consequence of the mitochondrial dysfunction ( Kim et al, 2021 ). High levels of ROS triggers oxidant stress, which leads to cellular damages, tumor progression, and chemotherapy resistance ( Brozovic et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%